2016
DOI: 10.1080/21655979.2016.1164370
|View full text |Cite
|
Sign up to set email alerts
|

Production of a novel bioflocculant and its flocculation performance in aluminum removal

Abstract: A novel bioflocculant CBF with high flocculating activity, produced by mixed culture of Rhizobium radiobacter F2 and Bacillus sphaericus F6 from soil, was investigated with regard to its production and flocculation performance in Al(III) removal. The most preferred carbon source, nitrogen source and C/N ratio (w/w) for strains F2 and F6 to produce CBF were glucose, urea and 20, respectively. The optimal inoculum size for CBF production was 10 % (v/v). The optimal initial pH, culture temperature and shaking spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…The metabolism of microorganisms is directly related to culture temperature [ 2 , 32 ]. Maximum enzymatic activation can only be obtained at an optimum temperature [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism of microorganisms is directly related to culture temperature [ 2 , 32 ]. Maximum enzymatic activation can only be obtained at an optimum temperature [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The shaking speed of 160 rpm was used in the following experimental studies. The shaking speed determines the dissolved oxygen concentration, which can also affect nutrient absorption and enzymatic reaction [ 36 ]. In the course of the early growth phase, the biomass and bioflocculant production were lower, resulting in lower viscosity of culture broth and oxygen demand, when the strain B. salmalaya 139SI proceed in the logarithmic and stationary phases, the biomass and the bioflocculant production increased, and the corresponding viscosity of the culture broth and the oxygen demand also increased.…”
Section: Resultsmentioning
confidence: 99%
“…In low pH, from 2 to 3.5, the strain failed to grow and biomass yield was the lowest in comparing to other variants. The same was observed in Apart from substrates, cations, and pH, the temperature is also a crucial factor in the production of bioflocculants, like other secondary metabolites (Xia et al 2008;Li et al 2015). Maximum activity of enzymes occurs also at an optimum temperature (Xia et al 2008).…”
Section: Ph and Temperature Impactmentioning
confidence: 54%
“…The strain failed to yield the cell biomass and the bioflocculant synthesis in lower ([25°C) or elevated ([35°C) temperature intervals. It was reported that for bioflocculant production by bacteria and their consortia, an optimal temperature is 28-30°C (Xiong et al 2010;Yang et al 2012;Nwodo et al 2014;Li et al 2015).…”
Section: Ph and Temperature Impactmentioning
confidence: 99%
“…The raw water characteristics were as follows: the temperature was 20.2 °C, pH was 7.6, turbidity was 2440.0 NTU, and COD was 2037.1 mg/l. The bioflocculant is primarily composed of polysaccharides (90.6 %) and protein (9.3 %) with a molecular weight of 10 5 -10 6 Da (Li, Ma, & Zuo, 2016). The fermentation conditions were shaking at 140 rpm/min, 30 °C, and fermentation for 24 hours.…”
Section: Methodsmentioning
confidence: 99%